Faktor Risiko Kejadian Demam Berdarah Dengue (DBD) pada Anak Usia 10-14 Tahun di Wilayah Kerja Puskesmas Temindung Kota Samarinda - Nindy Nurhalizah; Siswanto, Siswanto; Irfansyah Baharuddin Pakki; Muhamad Zakki Saefurrohim; Rina Tri Agustini (Yayasan Literasi Sains Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health issue in Indonesia. In 2023, a total of 114,720 DHF cases were reported nationwide, with an incidence rate (IR) of 41.4 per 100,000 population—still far above the national target. East Kalimantan is one of the provinces with the highest IR (147.33/100,000). Samarinda City is among the top three areas with the highest number of cases. One of the affected areas in Samarinda is Temindung Public Health Center, which recorded 83 DHF cases, with 52% occurring in children aged 10–14 years, indicating that this age group is the most vulnerable to DHF. This study aimed to analyze the risk factors associated with DHF incidence among children aged 10–14 years in the working area of Temindung Public Health Center. A quantitative approach was used with a case-control study design and total sampling of 81 respondents, consisting of 27 cases and 54 controls. Data analysis was conducted using the Chi-Square test and Odds Ratio (OR) calculation. The results showed significant associations maternal knowledge (p= 0.001; OR= 11.440), PSN behavior (p= 0.001; OR= 7.231), cadre support (p= 0.022; OR= 3.571), and health facilities availability (p= 0.034; OR= 9.100). Therefore, it’s recommended to involve students as mosquito larvae monitors, conduct thematic health education with PSN practice demonstrations, and optimize the distribution of facilities through Musrenbang and CSR-based partnerships.